2017
DOI: 10.1016/j.yexcr.2017.03.027
|View full text |Cite
|
Sign up to set email alerts
|

The functional interplay between the HIF pathway and the ubiquitin system – more than a one-way road

Abstract: The hypoxia inducible factor (HIF) pathway and the ubiquitin system represent major cellular processes that are involved in the regulation of a plethora of cellular signaling pathways and tissue functions. The ubiquitin system controls the ubiquitination of proteins, which is the covalent linkage of one or several ubiquitin molecules to specific targets. This ubiquitination is catalyzed by approximately 1000 different E3 ubiquitin ligases and can lead to different effects, depending on the type of internal ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 112 publications
1
25
0
Order By: Relevance
“…Our results showed that HIF-1 α , but not p53 and Myc, was regulated by GPC3. It has been well established that the degradation by prolyl hydroxylases (PHDs) is one of the most common ways in the regulation of HIF-1 α expression [27, 28]. In the present study, our data showed that knockdown of GPC3 resulted in decreased expression of HIF-1 α at protein level but not at mRNA level, suggesting that GPC3 regulates the expression HIF-1 α at the posttranscriptional level.…”
Section: Discussionsupporting
confidence: 51%
“…Our results showed that HIF-1 α , but not p53 and Myc, was regulated by GPC3. It has been well established that the degradation by prolyl hydroxylases (PHDs) is one of the most common ways in the regulation of HIF-1 α expression [27, 28]. In the present study, our data showed that knockdown of GPC3 resulted in decreased expression of HIF-1 α at protein level but not at mRNA level, suggesting that GPC3 regulates the expression HIF-1 α at the posttranscriptional level.…”
Section: Discussionsupporting
confidence: 51%
“…Cancer cells overcome the hypoxic conditions caused by their high proliferation and low angiogenesis rate through upregulating proangiogenic proteins. Under normoxic conditions, HIF-1α complexed with VHL binds to an E3 protein ligase, which results in polyubiquitination and proteasomal degradation [106]. Under hypoxic conditions, HIF-1α accumulates, dimerizes with HIF-1β, translocates into the nucleus, and induces the expression of target genes in the hypoxia response element (HRE) (Figure 3).…”
Section: Metabolic Shifts In Cancer: Glycolysis and Oxidative Phosphomentioning
confidence: 99%
“…HIF‐1α activity is regulated through its breakdown by prolyl hydroxylase domain protein and the von Hippel‐Lindau (VHL) ubiquitin ligase system . Constitutively expressed HIF‐1α protein is subjected to continuous proteolytic degradation by the proteasome in normoxic conditions through hydroxylation at the specific proline residues by prolyl hydroxylase domain protein (PHD) .…”
Section: Hypoxia‐inducible Factor 1‐alphamentioning
confidence: 99%
“…Constitutively expressed HIF‐1α protein is subjected to continuous proteolytic degradation by the proteasome in normoxic conditions through hydroxylation at the specific proline residues by prolyl hydroxylase domain protein (PHD) . The hydroxylation of proline residues allows VHL ubiquitin ligase complex to recognize HIF‐1α, producing polyubiquitination, and proteasomal degradation . PHD requires oxygen, iron, and 2‐oxoglutarate as cofactors .…”
Section: Hypoxia‐inducible Factor 1‐alphamentioning
confidence: 99%